Enteric Infections Are Common in Patients with Flares of Inflammatory Bowel Disease. (October 2018) - Axelrad, Jordan; Joelson, Andrew; Green, Peter; Lawlor, Garrett; Lichtiger, Simon; Cadwell, Ken; Lebwohl, Benjamin
Abstract OBJECTIVES Few studies have examined the role of non-Clostridium difficile enteric infections in flares of inflammatory bowel disease (IBD). Our objective was to investigate enteric infection detected by multiplex PCR stool testing in patients with IBD. Methods We performed a cross-sectional analysis of 9403 patients who underwent 13, 231 stool tests with a gastrointestinal pathogen PCR panel during a diarrheal illness from March 2015 to May 2017. Our primary outcome was the presence of an infection. Secondary outcomes included endoscopic and histologic predictors of infection, and IBD outcomes following testing. Results A total of 277 patients with Crohn's disease (CD), 300 patients with ulcerative colitis (UC), and 8826 patients without IBD underwent 454, 503, and 12, 275 tests, respectively. Compared to patients without IBD, patients with IBD were less likely to test positive (CD 18.1%, UC 16.1%, no IBD 26.6%, p < 0.001). Compared to patients without IBD, CD had a higher prevalence of norovirus (p = 0.05) andCampylobacter (p = 0.043), whereas UC had a lower prevalence of norovirus (p = 0.001) and a higher prevalence ofCampylobacter (p = 0.013), Plesiomonas (p = 0.049), andEscherichia coli species (p < 0.001). Of 77 patients who underwent endoscopy, there were no major endoscopic or histologic predictors of a positive test. Patients who tested negative were more likely to have IBD therapy escalated (p = 0.004). Enteric infection did not impact IBD outcomes following testing (log-rank 0.224). Conclusions Non-Clostridium difficile enteric infections were identified in 17% of symptomatic patients with IBD. Endoscopic and histologic findings may not differentiate flare from infection. Norovirus andE.coli may play an important role in flare of IBD.